Enhancing Rural Areas while Safeguarding Ecosystems through Sustainable Practice of Ecosystem Based Approaches (EBA) with Emphasis on Ecotourism - Iakovoglou, Valasia; Zaimes, George N. (International Journal of Bio-resource and Stress Management, 2018)
Sustaining the healthy function and structure of natural ecosystems is a challenge, mainly due to the negative impacts of anthropogenic activities and climate change. The complexity of safeguarding ecosystems has led to the need of new management tools that prioritize their long-term sustainability. Such a tool is the “Ecosystem Based Approaches (EBA)”, a newly developed management practice that has showed great promise because it benefits the long-term healthy structure and function of ecosystems. EBA has been implemented successfully in the USA, but only recently has been introduced in areas such as the Mediterranean region, while in other areas like Africa its application is not known, yet. Further, “Ecotourism” is a newly fast growing trend in the tourism sector that can provide increased economic growth. The scope of this paper is to introduce both “EBA” and “Ecotourism” in order to benefit rural areas and protect the adjacent ecosystems. Specifically, it is a great challenge to develop an EBA management plan tailored to safeguard ecosystems, particularly highly venerable areas such as the protected (e.g. Natura, 2000), while emphasizing sustainable Ecotourism activities to enhance rural areas. Further, this paper provides insights on “baseline” information necessary to be used as guidelines when developing and implementing such a sustainable plan that suits each ecosystem. This will allow the understanding of EBA in developing sustainable ecotourism activities that will enhance job opportunities for rural areas.